A Study of Matrices for High–Intensity Magnetic Separators. (1995) - Maly, V. M.
Abstract : This paper summarises the results of the research carried out, for the last 15 years, by the Department of Separation of Weakly Magnetic Ores of the Mekhanobrchermet Institute, Krivoy Rog, Ukraine, on the matrices of high–intensity magnetic separators foe beneficiation of weakly magnetic iron ores and other weakly magnetic materials.